Evaluasi Program Sistem Pengolahan Tinja Komunal Untuk Peningkatan Kualitas Sanitasi Wilayah Pesisir di Kota Batam - Ahmadi, Ahmadi; Nurjading, Rasmin; Sari, Novela (Jurnal Sanitasi Lingkungan, 2025)
Background: One of the pillars of sustainable national health development is the availability of adequate, accessible, and affordable sanitation facilities, such as access to safe toilets (human waste treatment). The 2022 Economics of Sanitation Initiative (ESI) survey reported that we are currently facing a global sanitation crisis, with 3.6 billion people still living with poor-quality toilets that harm health and pollute the environment. Additionally, more than 800 children die from diarrheal diseases due to unsafe water and poor sanitation. This study focuses on coastal areas in Batam City where communal fecal sludge treatment systems have been installed, specifically in Sekanak Raya Sub-district and Pulau Kasu, Belakang Padang District, Batam City. Methods: This study employed a quantitative method using a descriptive observational approach. The sampling technique used was total sampling, involving all households connected to the communal fecal sludge treatment system in the study locations, totaling 60 households. The variables analyzed included leakage status, odor generation, and clogging in the communal sludge treatment system. Results: The majority of the systems exhibited leakage (66.7%), odor generation (90.0%), and clogging (90.0%), particularly in the installation located in Sekanak Raya Sub-district. Conclusion: The analysis indicates that the communal fecal sludge treatment systems installed in the study areas are categorized as ineffective, as evidenced by the presence of leakage, odor issues, and clogging. Further research is needed to identify the factors affecting the effectiveness of the communal sludge treatment system, including community attitudes, defecation habits, and the technical suitability of the system installation.